Khotbah Ekspositori sebagai Jembatan antara Teks Suci dengan Konteks Kehidupan: Sebuah Studi pada Gereja Pantekosta Tabernakel Surabaya - Lumbanbatu, Arjuna; Sugiharto, Ayub (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2024)
Understanding the teachings of the Bible is a need of the congregation throughout the history of the church. In particular, today's congregation in the midst of the development of the digital world, is required to understand its faith correctly and relevant to the times. The Bible is the highest authority in the teaching and practical life of the congregation, especially in the Tabernacle Pentecostal Church - Christ the Helper. However, for the congregation of the Tabernacle Pentecostal Church - Christ the Helper, understanding the Bible is not easy, because there is a gap between the text of the Bible and the context of this congregation living in the present. There are differences in language, socio-cultural, political and religious that are very contrasting between the context of the Bible and the present. Expository preaching plays an important role as a bridge between the text of the Bible and the congregation. Through a descriptive qualitative method, the research was conducted by collecting and analyzing library data and then comparing it with the factual situation in the field. In addition, observations were made of sermon archives at the Tabernacle Pentecostal Church - Christ the Helper in the last four years, as well as short interviews related to the development of the topics discussed with several congregations. From the research, it was found that expository preaching is able to bridge the Bible text with today's congregation, specifically in the Tabernacle Pentecostal Church - Christ the Helper. First, expository preaching rephrases the Bible's teachings into today's language; second, expository preaching structures the sermon in a systematic way that is easy for the congregation to understand; third, it helps the congregation participate in Bible teaching; and fourth, it increases the congregation's interest in Biblical teaching.   Abstrak Memahami pengajaran Alkitab adalah kebutuhan jemaat sepanjang sejarah gereja. Secara khusus jemaat masa kini ditengah-tengah perkembangan dunia digital, diharuskan untuk mengerti imannya secara benar dan relevan dengan zaman. Alkitab adalah otoritas tertinggi dalam pengajaran maupun kehidupan praktis jemaat, khususnya di Gereja Pantekosta Tabernakel - Kristus Penolong. Namun bagi jemaat Gereja Pantekosta Tabernakel - Kristus Penolong, memahami Alkitab bukanlah hal yang mudah, karena adanya kesenjangan antara teks Alkitab dengan konteks jemaat ini yang hidup di masa kini. Ada perbedaan bahasa, sosial budaya, politik serta keagamaan yang sangat kontras antara konteks Alkitab dan masa kini. Khotbah ekspositori menjadi penting peranannya sebagai jembatan antara teks Alkitab dan jemaat. Melalui metode kualitatif deskriptif, penelitian dilakukan dengan pengumpulan dan analisa data-data kepustakaan kemudian dikomparasi dengan situasi faktual di lapangan. Selain itu dilakukan pengamatan terhadap arsip-arsip khotbah di Gereja Pantekosta Tabernakel - Kristus Penolong empat tahun belakangan ini, juga wawancara singkat terkait perkembangan topik yang dibahas dengan beberapa jemaat. Dari penelitian diperoleh fakta bahwa khotbah ekspositori mampu menjembatani antara teks Alkitab dengan jemaat masa kini, secara khusus di Gereja Pantekosta Tabernakel - Kristus Penolong. Pertama, khotbah ekspositori membahasakan ulang pengajaran Alkitab kepada bahasa masa kini; kedua, khotbah ekspositori menyusun khotbah dalam sistematika yang mudah untuk dipahami jemaat; ketiga, membantu partisipasi jemaat terhadap pengajaran Alkitab; dan keempat, meningkatkan minat jemaat terhadap pengajaran yang Biblikal.